Miliary tuberculosis in an immunocompetent patient: Case report: Tuberculosis miliar en paciente inmunocompetente: Reporte de caso - Valle Farfan, Renzo Steffano (2024)
Milar Tuberculosis (TB) is a presentation with a fatal outcome if it is not diagnosed or treated on time; although certain conditions are required to develop this presentation. In this In this article, the case of a 48-year-old man with no pathological history is studied, who started the disease with a time of six months with an initial diffuse gastrointestinal pain and later one month before admission presented progressive respiratory symptoms; he was admitted for emergencies where bilateral diffuse miliary compromise was evident in the chest computed tomography; upon admission, he was administered oxygen and support measures, an HIV test was obtained which was negative, and positive results were obtained in the sputum smear microscopy. His clinical evolution was stationary until the administration of antituberculosis therapy, observing slight clinical improvement, likewise, low doses of corticosteroids were administered after which a favorable evolution was demonstrated and he was discharged.